Bald eagle - Goldsworthy, Kaite (New York : AV2 by Weigl, 2013)
Photographs and simple text provide an introduction to the Bald eagle.
1.7
K-3
Keywords: Bald eagle -- United States -- Juvenile literature; Signs and symbols -- United States -- Juvenile literature; Bald eagle; Signs and symbols; Bald eagles; Signs and symbols -- United States; Bald eagle; Signs and symbols; Birds of prey; United States -- Seal -- Juvenile literature; United States -- Seal; United States -- Seal; Readers (Elementary)